Pemanfaatan Batu Sungai Karawa Kabupaten Pinrang Sebagai Agregat Campuran Laston Lapis Antara - Egipto Buli; Alpius; Louise Elizabeth Radjawane (Paulus Civil Engineering Journal, 2022)
Utilization of local materials for road building materials needs not to be optimized, especially around the Karawa area, so that currently road building materials are still using materials from other regions. This study aims to determine the characteristics of the Karawa River stone, asphalt characteristics, specific gravity of the filler and to obtain the composition of the mixture, as well as the characteristics of the mixture through the conventional marshall test and the marshall immersion test used to determine the stability of the remaining marshall using optimal asphalt content. The results showed that the characteristics of the pavement material in the form of river stone from the Karawa River in Pinrang Regency as an intermediate mixture aggregate met the requirements for road pavement material. The characteristics of the intermediate mixture with asphalt content of 5.0%, 5.5%, 6.0%, 6.5%, and 7.0% were determined using the Marshall test. The remaining marshall stability of 97.47% meets the 2018 Bina Marga standard, which is at least 90%, through the results of the marshall immersion test for layers between asphalt mixtures with an optimum asphalt content of 6.0%.